The Impact of Feedback in The Process of Peer Assessment on Students Recount Writing - Nur Laili Indasari; Oikurema Purwati (Universitas Negeri Surabaya, 2018)
Providing feedback to peers writing is not an easy task. It is required an ability to deliver the feedback or comment critically and a competence to master the knowledge of writing. Therefore, the present study is going to explore the impact of giving feedback to the students writing and to acknowledge what the students challenge while giving feedback to their peers writing. There are 10 students as the participants of this study. Qualitative study assists the researchers to get the data. The results revealed that the comparison between students first draft and the last draft had improvements mainly on the aspect of the language use. Meanwhile, most students challenges while giving feedback to the peers writing were they had to have knowledge about the grammar mainly the use of simple past tense before giving feedback to their peer. Keywords: writing, peer assessment, feedback, challenge